Atmospheric responses to idealized urban land surface forcing in eastern China during the boreal spring. Issue 19 (6th October 2015) - Deng, Jiechun; Xu, Haiming
Abstract In contrast to the impacts of anthropogenic aerosols and greenhouse gases, little is known about the impact of urban land surface forcing (ULSF) on large‐scale atmospheric circulation. This study explores atmospheric responses to idealized ULSF in eastern China during the boreal spring using the Community Atmosphere Model version 5.1 coupled with the Community Land Model version 4. Results show that the ULSF leads to an increased air temperature in northern China both near the surface and in the lower troposphere. Related to a strong thermal feedback loop, a middle‐upper tropospheric cooling is found in eastern China while a relatively strong warming occurs in the middle‐high latitudes, which acts to enhance the meridional temperature gradient to the north of the source region and then shifts the East Asian subtropical jet stream (EASJ) southward. A weakened southwesterly in the lower troposphere in southern China slows down moisture transportation to northern China, and the southward shifted EASJ induces strong anomalous sinking motion to the north of the Yangtze River Valley (YRV). The associated changes in moisture and vertical airflow result in moisture divergence along the YRV and convergence in southern China. Thus, the spring rain belt is shifted southward, as characterized by below‐normal rainfall extending from the Huai River Valley to South Korea and above‐normal rainfall from southern China to the south coast of Japan. In addition, analysis of the upper tropospheric wave activity signifies that large‐scale atmospheric responses due to the ULSF also exert an important influence on local climate.